2020
DOI: 10.3390/membranes10120419
|View full text |Cite
|
Sign up to set email alerts
|

Aging of Thin-Film Composite Membranes Based on Crosslinked PTMSP/PEI Loaded with Highly Porous Carbon Nanoparticles of Infrared Pyrolyzed Polyacrylonitrile

Abstract: The mitigation of the physical aging of thin-film composite (TFC) poly[1-trimethylsilyl-1-propyne] (PTMSP) membranes was studied via the simultaneous application of a polymer-selective layer crosslinking and mixed-matrix membrane approach. For the first time, a recently developed highly porous activated carbon material (infrared (IR) pyrolyzed poly[acrylonitrile] (PAN) or IR-PAN-a) was investigated as an additive to a PTMSP-selective layer for the reduction of aging in TFC membranes. The total electric energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The size distributions of HCPS particles obtained after grinding the initial commercial MN200 samples were determined by dynamic light scattering on a Malvern Zetasizer Nano analyzer (Malvern Panalytical Ltd., Malvern, Worcestershire, UK) [ 46 ]. The test samples were prepared by suspending the particles in chloroform (0.06 g of a sample in 10 mL of solvent).…”
Section: Methodsmentioning
confidence: 99%
“…The size distributions of HCPS particles obtained after grinding the initial commercial MN200 samples were determined by dynamic light scattering on a Malvern Zetasizer Nano analyzer (Malvern Panalytical Ltd., Malvern, Worcestershire, UK) [ 46 ]. The test samples were prepared by suspending the particles in chloroform (0.06 g of a sample in 10 mL of solvent).…”
Section: Methodsmentioning
confidence: 99%
“…PTMSP is a highly permeable glassy polymer that possesses an unrelaxed free fractional volume (FFV) and due to that undergoes physical aging because of the chain rearrangement, resulting in the reduction of the membrane permeance. 71 Therefore, one major concern when using this polymer as gutter layer is its aging. Chen et al 72 demonstrated that a thin coating of PTMSP can lose up to 80% of the CO 2 permeance within 14 days.…”
Section: Incorporation Of Zif-8 and Zif-94 (Sale)mentioning
confidence: 99%
“…The size distributions of HCPS particles obtained after grinding the initial commercial MN200 samples were determined by dynamic light scattering on a Malvern Zetasizer Nano analyzer (Malvern Panalytical Ltd., Malvern, UK) [33]. The test samples were prepared by suspending the particles in chloroform (0.06 g of a sample in 10 mL of solvent).…”
Section: Particle Size Distributionmentioning
confidence: 99%
“…One of the simplest and most effective ways to reduce membrane aging is to introduce a filler phase to produce so-called mixed-matrix membranes (MMM) [21][22][23]. Molecular sieves [24], structures based on metal-organic frameworks (MOF) [25][26][27][28], porous aromatic frameworks (PAF) [16,[29][30][31][32][33], hyper-crosslinked polystyrene (HCPS) [34][35][36][37][38], graphene, and graphene oxide (GO) [39] are used as such additives. MOF, such as zeolitic imidazolate frameworks (ZIF-7, -8), can increase the gas permeability, selectivity, and mechanical properties of membranes [26,27].…”
Section: Introductionmentioning
confidence: 99%